2009
DOI: 10.1083/jcb.200804038
|View full text |Cite
|
Sign up to set email alerts
|

Erk1/2 MAP kinases are required for epidermal G2/M progression

Abstract: Erk1/2 mitogen-activated protein kinases (MAPKs) are often hyperactivated in human cancers, where they affect multiple processes, including proliferation. However, the effects of Erk1/2 loss in normal epithelial tissue, the setting of most extracellular signal-regulated kinase (Erk)–associated neoplasms, are unknown. In epidermis, loss of Erk1 or Erk2 individually has no effect, whereas simultaneous Erk1/2 depletion inhibits cell division, demonstrating that these MAPKs are necessary for normal tissue self-ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 48 publications
4
67
0
Order By: Relevance
“…Similarly, Si et al showed that downregulation of Erk1/2 by siRNA inhibited the growth and invasion of human osteosarcoma cells, and found that the knockdown of Erk1/2 made cancer cells more sensitive to cisplatin treatment (57). Moreover, Dumesic et al reported that combined siRNA-induced knockdown of Erk1/2 caused epidermal hypoplasia and hypoproliferation without disrupting differentiation in human epidermis (58). Finally, Duvvuri et al found that genetic inactivation of Erk1/2 using siRNA abrogated the Erk1/2 mediated growth effects of TMEM16A in HNSCC (53).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Si et al showed that downregulation of Erk1/2 by siRNA inhibited the growth and invasion of human osteosarcoma cells, and found that the knockdown of Erk1/2 made cancer cells more sensitive to cisplatin treatment (57). Moreover, Dumesic et al reported that combined siRNA-induced knockdown of Erk1/2 caused epidermal hypoplasia and hypoproliferation without disrupting differentiation in human epidermis (58). Finally, Duvvuri et al found that genetic inactivation of Erk1/2 using siRNA abrogated the Erk1/2 mediated growth effects of TMEM16A in HNSCC (53).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the extracellular signalregulated kinase 1/2 (Erk1/2)-MAPK pathway supports keratinocyte proliferation and must be dampened to allow for cell cycle exit and differentiation. 136 EphA2 acts in a ligand-dependent manner to attenuate Erk1/2 signaling in a variety of epithelial cells, including keratinocytes. 43,[137][138][139] A role for Eph receptor and ephrin signaling in epidermal growth control is further supported by the observation that injection of recombinant proteins containing ectodomain fragments of Eph receptors or ephrin ligands increased keratinocyte proliferation in the epidermis and hair follicles.…”
Section: Eph Receptor and Ephrin Function In Epidermal Homeostasismentioning
confidence: 99%
“…Deletion of Mek1/2 results in decreased proliferation, leading to epidermal hypoplasia (Scholl et al 2007). Simultaneous deletion of Erk1/2 also results in proliferation defects and hypoplasia (Dumesic et al 2009). Conversely, activation of Ras, Raf, or the downstream Mek1 in the skin results in hyperproliferation accompanied by epidermal hyperplasia and downregulation of differentiation markers (Tarutani et al 2003;Scholl et al 2004).…”
Section: Epidermal Stratification Renewal and Differentiationmentioning
confidence: 99%